2020
DOI: 10.17582/journal.pjz/20190402110434
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Listeria monocytogenes from Raw Vegetables and Meat Sold in Quetta, Pakistan

Abstract: Authors' Contribution AS, FA and TMA designed the experiments. AS, MN and HA performed the experiments. TMA, JR and RA analyzed the data. All authors contributed in Manuscript writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Although RTE food sold by street vendors is cheap in price, its microbial quality may be compromised if proper hygienic measures are not adopted. In developing countries such as Pakistan, such measures are often neglected, and food items have been reported to be contaminated with several pathogens (Samad et al, 2018a(Samad et al, , b, 2019(Samad et al, , 2020. The results of the present study are alarming, as none of the RTE food samples tested (n = 320) were free of bacteria.…”
Section: Discussioncontrasting
confidence: 53%
“…Although RTE food sold by street vendors is cheap in price, its microbial quality may be compromised if proper hygienic measures are not adopted. In developing countries such as Pakistan, such measures are often neglected, and food items have been reported to be contaminated with several pathogens (Samad et al, 2018a(Samad et al, , b, 2019(Samad et al, , 2020. The results of the present study are alarming, as none of the RTE food samples tested (n = 320) were free of bacteria.…”
Section: Discussioncontrasting
confidence: 53%
“…Also, it is believed to have a dual intercellular lifestyle, which helps it to invade, colonise and establish in a host [5]. Common food that can easily be contaminated includes dairy [6], vegetables [7, 8], meat and poultry [9,10]. A recent survey [11] found that serogroup 1/2a-3a dominate food, 4a-4c in livestock, and 1/2a-3a in humans.…”
Section: Introductionmentioning
confidence: 99%